Burger Time ou les Tentations de saint Antoine, or Not Wanting to Say Anything About Mauro Lanza, Gustave Flaubert and Peter Pepper - Andrea Valle (Flaubert: Revue Critique et Génétique)
The article discusses Burger Time ou les Tentations de Saint Antoine, a 12-minute work of electronic music composed by Mauro Lanza. In particular, it proposes a three-layer interpretative methodology, focusing respectively on audible perception, on signal analysis and finally on a semiotic framework. In the first layer, the music work is discussed in terms of audible figures, and an annotated visual score is proposed as a result. In the second one, categories for signal analysis are introduced and the gathered data are used to build a structural matrix aiming at defining the identity of the previously identified figures. Finally, the third layer proposed an integrated semiotic interpretation by taking into account the previous layers and a textual document, in order to highlight the most relevant semantic “isotopies”.